Validity of the 20 Meter Multi-Stage Shuttle Run Test (MSSRT) In Predicting VO2 Max - Kumar, A. Shasi (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
The purpose of this study was to investigate the validity of the 20 meter multi-stage shuttle run test (MST) in predicting VO2max compared to the directly measured reading from the laboratory. 4 male participants, who were diverse in terms of their ages and who were active physically, performed the MST and an incremental treadmill tests. Predicted VO2max values were obtained for the MST based on their stages and shuttles and actual VO2max values were obtained from the laboratory treadmill test. Results showed that all predicted VO2max values for the MST over-predicted that of the actual VO2max values from the laboratory test. This study seems to suggest that there is no validity in the MST in predicting VO2max of an individual as compared to the actual VO2max values from the laboratory.